Effect of Y3+ on the local structure and luminescent properties of La3−xYxSi6N11:Ce3+ phosphors for high power LED lighting. Issue 80 (15th August 2016) - Du, Fu; Zhuang, Weidong; Liu, Ronghui; Liu, Yuanhong; Zhong, Jiyou; Gao, Wei; Chen, Kai; Chen, Lei; Kato, Kenichi; Lin, Kun
Abstract : A series of phase pure nitride yellow phosphors La3− x Y x Si6 N11 :Ce 3+ with good thermal stability and tunable luminescence properties have been synthesized and the crystal structure was investigated in detail. Abstract : A series of Ce 3+ -activated La3− x Y x Si6 N11 yellow phosphors were synthesized by high temperature solid-state reaction; their structures and luminescent properties were systematically investigated. The results of structural and spectral characterization showed that with the increase of Y 3+ replacing La 3+ in La3− x Y x Si6 N11 :Ce 3+ (0 < x ≤ 0.9), the space group remains P 4 bm but with Y 3+ occupying two crystallographic sites in different ratio, while the emission spectra exhibit a red-shift from 535 nm to 552 nm. Moreover, the thermal quenching properties of La2.86− x Y x Si6 N11 :0.14Ce 3+ exhibit somewhat of a decrease with the increase of x value, but still remains at 95% ( x = 0.9) of the initial emission intensity measured at 200 °C. In addition, the light quality is significantly improved by direct packaging with a blue LED chip. The above results indicate that La3− x Y x Si6 N11 :Ce 3+ may be a promising phosphor for high power white-light LEDs.